Feeding with resistant maltodextrin suppresses excessive calorie intake in a high-fat diet, mediated by changes in mouse gut microbiota composition, appetite-related gut hormone secretion, and neuropeptide transcriptional levels - Ito, Kaede; Haraguchi, Atsushi; Sato, Shuhei; Sekiguchi, Masataka; Sasaki, Hiroyuki; Ryan, Conn; Lyu, Yijin; Shibata, Shigenobu (Frontiers in Microbiomes, 2023)
Consuming resistant maltodextrin (RMD) decreases food intake and increase appetite-related gut hormones, but the underlying mechanisms have remained unknown. Therefore, we aimed to elucidate the mechanisms underlying the effects of RMD feeding on food intake (appetite) using Institute of Cancer Research male mice fed with a high-fat diet (HFD-cellulose group) or HFD in which cellulose was replaced with RMD (HFD-RMD group). Feeding mice with an HFD-RMD for approximately 8 weeks inhibited excessive calorie intake and altered the gut microbiota composition. Excessive calorie intake was inhibited for several days in mice fed only with an HFD-cellulose and transplanted with fecal microbiota from the HFD-RMD group (FMT-HFD-RMD group). Moreover, in the HFD-RMD and FMT-HFD-RMD groups, serum active glucagon-like peptide (GLP)-1 and peptide tyrosine tyrosine (PYY) levels were significantly higher, and appetite-related neuropeptide gene transcription in the hypothalamus were significantly altered, compared with the HFD-cellulose and FMT-HFD-cellulose groups. These results suggested that the long-term RMD intake changed the gut microbiota composition, increased the GLP-1 and PYY secretion, and altered the appetite-related neuropeptide gene transcription in the hypothalamus, leading to suppressed excessive calorie intake in an HFD.